A new species of the genus Dysommina (Teleostei: Anguilliformes: Synaphobranchidae: Ilyophinae) from the Western Pacific - Tighe, Kenneth A.; Ho, Hsuan-Ching; Hatooka, Kiyotaka (Zootaxa, 2018)
Dysommina orientalis, a new species of Ilyophine eel from off Taiwan and Japan is described and illustrated. The species had long been recognized as Dysommina rugosa in the western Pacific and is distinguished from D. rugosa by a lower number of predorsal vertebrae, a higher number of total vertebrae, shorter head length, smaller eye size, reduced vomerine dentition, and an increased number of both mandibular and maxillary teeth, as well as significant differences in DNA sequence in COI and 16S.